Examining the Mediating Impact of Attitude Towards Mobile App Use on the Relationship between TAM Factors and Consumers' Purchase Intentions - Satti, Zoya Wajid; Khan, Muhammad Omair (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to check the relationship between TAM factors and purchase intention, having the mediating role of technological information. Research is being conducted to determine how Covid 19 affects consumer purchase intentions. Investigation shows that around the world, there has been an agenda to inspect TAM factors and how they impacted purchasing behaviours because of Covid. Individuals move towards web-based shopping as they effectively embrace early adopter conduct and move towards innovation. They need to look at whether they will be severe towards the creation of internet shopping in post-pandemic time. Data was collected through structured questionnaires and analyzed through Smart Pls. Consumer shopping behaviour, the theory of planned behaviour, supports our research questions. There is a positive mediation relationship between TAM factors and CPI during Covid 19, but before COVID-19, mediation fails. The prime focus of this study is to investigate behavioural change of customers due to the pandemic, which is helpful for strategy makers to formulate new strategies according to new norms of society.